(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
The present problem is concerned with the study of deformation of a rotating generalized thermoelastic medium under the influence of gravity. The components of displacement, force stress and temperature distribution are obtained in Laplace and Fourier domain by applying integral transforms. These components are then obtained in the physical domain by applying a numerical inversion method. Some particular cases are also discussed in context of the problem. The results are also presented graphically to show the effect of rotation and gravity in the medium.